Mercury determination in biological organism in the estuary of Muar River, West Johor, Malaysia - Rahman, Md. Mokhlesur; Ansary, R. H.; Fuad, Miskon; Yunus, Kamaruzzaman; Wan Nik, Wan Sani (Researcher Society of Chemical Sciences, 2016)
Determination of Mercury in Biological Sample in Muar River Estuary, West Johor, Malaysia. This study was carried out at the Estuary of Muar River, west Johor, Malaysia. Different types of biota species namely Crassostrea irredalei, Perna viridis and Anadara granosa were collected all through the torrential rainy season in November 2005. These biota species were dried and then cooked in an acid solution for Cold Vapour Atomic Absorption Spectrometric (CV-AAS) analysis. CV-AAS) was used for decisive the mercury (Hg++) concentration in the collected biota species. The average Hg++ concentration in C. irredalei, P. viridis and A. granosa were 1.854 ± 1.012 μg g-1, 0.336 ± 1.125 μg g-1 and 1.178 ± 1.182 μg g-1 respectively. These results directed that the biota especially C. irredalei and A. granosa are contaminated by Hg++ and these are not safe to be consumed for publicly used due to the total Hg++ concentration exceeding 0.5 μg g-1 according to WHO.